Sex‐specific behavioral traits in the Brd2 mouse model of juvenile myoclonic epilepsy. (28th August 2014) - Chachua, T.; Goletiani, C.; Maglakelidze, G.; Sidyelyeva, G.; Daniel, M.; Morris, E.; Miller, J.; Shang, E.; Wolgemuth, D. J.; Greenberg, D. A.; Velíšková, J.; Velíšek, L.
<x xml:space="preserve">Abstract</x> Idiopathic generalized epilepsy represents about 30–35% of all epilepsies in humans. The bromodomain BRD2 gene has been repeatedly associated with the subsyndrome of juvenile myoclonic epilepsy (JME). Our previous work determined that mice haploinsufficient in Brd2 (Brd2+/−) have increased susceptibility to provoked seizures, develop spontaneous seizures and have significantly decreased gamma‐aminobutyric acid (GABA) markers in the direct basal ganglia pathway as well as in the neocortex and superior colliculus. Here, we tested male and female Brd2+/− and wild‐type littermate mice in a battery of behavioral tests (open field, tube dominance test, elevated plus maze, Morris water maze and Barnes maze) to identify whether Brd2 haploinsufficiency is associated with the human behavioral patterns, the so‐called JME personality. Brd2+/− females but not males consistently displayed decreased anxiety. Furthermore, we found a highly significant dominance trait (aggression) in the Brd2+/− mice compared with the wild type, more pronounced in females. Brd2+/− mice of either sex did not differ from wild‐type mice in spatial learning and memory tests. Compared with wild‐type littermates, we found decreased numbers of GABA neurons in the basolateral amygdala, which is consistent with the increase in aggressive behavior. Our results indicate that Brd2+/− haploinsufficient mice show no cognitive impairment but have behavioral traits similar to those found in patients with JME (recklessness, aggression). This suggests that either the BRD2 gene is directly responsible for influencing many traits of JME or it controls upstream regulators of individual phenotypes.